In Vitro Antibacterial Susceptibility of Different Pathogens to Thirty Nano-Polyoxometalates - Ștefana Bâlici; Dan Rusu; Emőke Páll; Miuța Filip; Flore Chirilă; Gheorghe Zsolt Nicula; Mihaela Laura Vică; Rodica Ungur; Horea Vladi Matei; Nicodim Iosif Fiț (MDPI AG, 2021)
Due to their unique properties, nano-polyoxometalates (POMs) can be alternative chemotherapeutic agents instrumental in designing new antibiotics. In this research, we synthesized and characterized "smart" nanocompounds and validated their antibacterial effects in order to formulate and implement potential new drugs. We characterized thirty POMs in terms of antibacterial activity-structure relationship. The antibacterial effects of these compounds are directly dependent upon their structure and the type of bacterial strain tested. We identified three POMs that presented sound antibacterial activity against S. aureus, B. cereus, E. coli, S. enteritidis and P. aeruginosa strains. A newly synthesized compound K6[(VO)SiMo2W9O39]·11H2O (POM 7) presented antibacterial activity only against S. aureus (ATCC 6538P). Twelve POMs exerted antibacterial effects against both Gram-positive and Gram-negative strains. Only one POM (a cluster derivatized with organometallic fragments) exhibited a stronger effect compared to amoxicillin. New studies in terms of selectivity and specificity are required to clarify these extremely important aspects needed to be considered in drug design.